(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This paper will explore the impact of leadership styles and skills on teams and organisational objectives and is presented in two parts, namely: (a) Impact of leadership styles on team and organisational objectives: transactional leadership, transformational leadership, democratic leadership, authoritarian leadership, laissez-faire leadership; and (b) Impact of leadership skills on team and organisational objectives: create a safe environment that promotes trust, values open communications, connects work to organisation objectives, builds self-esteem and confidence, respects diverse cultures and customs, challenging beliefs and assumptions.